ChemInform Abstract: Bio‐Inspired Formal Synthesis of Hirsutellones A—C Featuring an Electrophilic Cyclization Triggered by Remote Lewis Acid‐Activation. Issue 19 (13th May 2014) - Li, Xu‐Wen; Ear, Alexandre; Roger, Lukas; Riache, Nassima; Deville, Alexandre; Nay, Bastien
Abstract A bio‐inspired strategy is used to complete the formal synthesis of the antitubercular hirsutellone B (I) and congeners A (II) and C (III), through construction of its decahydrofluorene core from a linear polyene strand activated at both ends by a silyl enol ether and an allyl acetate (not shown).